Dupilumab for treatment of primary cutaneous amyloidosis in adults: two case reports and literature review - Guo, Feiying; Zhong, Huajie; Wu, Yuan; Xu, Xue; Tan, Jiarong; Zhou, Qiang; Tang, Shunli (Frontiers in Medicine, 2025)
Lichenoid amyloidosis (LA), a subtype of primary cutaneous amyloidosis (PCA), is featured by intensely pruritic, hyperkeratotic papules which lacks standardized treatment. Dupilumab, a human monoclonal antibody targeting for interleukin (IL)-4/13 receptor α chain, is widely applied in type 2 inflammation diseases treatment. This article reported two cases of refractory LA successfully treated with dupilumab and reviewed publications reporting dupilumab treatment for PCA.